Peran Baitul Mall Wattamwil sebagai Upaya Pengentasan Kemiskinan melalui Pengembangan Usaha Mikro Kecil dan Menengah - Supanji Setyawan; Chaidir Iswanaji (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2021)
Poverty is one of the macroeconomic indicators in which Indonesia's economic development in aggregate shows a good picture and a decrease in the poverty level of the poor, but in terms of economic structure, segments of Indonesian society are still relatively lagging behind and relatively do not get real benefits from the results of development. Magelang Regency is one of the districts that have poverty problems. This poverty problem can be overcome by developing micro, small and medium enterprises (MSMEs), especially in the industrial sector, where this sector is the leading sector in Magelang Regency. The purpose of this study was to determine the effect of financing on the income of MSEs as customers of BMT Bima industrial business group and how the role of BMT in overcoming the problem of poverty through the functions of baitul mall and baitul tamwil. This study uses a simple linear regression analysis tool. The results obtained (1) the financing variable does not have a significant effect on the income variable of MSME customers of BMT Bima Magelang industrial business group, this is because there are still customers who use financing for personal economic activities, (2) BMT is able to reduce poverty levels by providing assistance that comes from zakat, infaq, sadaqah, and waqf and still persists by providing financing to MSME customers of the BMT Bima Magelang industry group